STUDI KUALITATIF KEBUTUHAN INFORMASI MEDIA TERHADAP MANAJEMEN DIRI PENDERITA DIABETES MELITUS DI KELURAHAN ANDALAS WILAYAH KERJA PUSKESMAS ANDALAS KOTA PADANG - Faadhilah, Tiara (Jurnal Promosi Kesehatan Poltekkes Bengkulu, 2025)
Diabetes mellitus is one of the leading non-communicable diseases causing death worldwide. The prevalence of pre-elderly individuals with diabetes mellitus in West Sumatra is 1.2%, totaling 18,138 people. Based on data from Andalas Public Health Center, diabetes mellitus ranks second with 987 reported cases. The purpose of this study was to obtain in-depth information regarding the information needs for self-management of diabetes mellitus patients in Andalas Sub-district, working area of Andalas Public Health Center, Padang City. This research employed a qualitative descriptive approach, conducted from May 22 to June 25, 2025. Data were collected through in-depth interviews with 7 pre-elderly non-Prolanis diabetes mellitus patients, 3 person in charge of PTM and Prolanis, one person responsible for health promotion, a design expert as key informants, and cadres from Posyandu Sejahtera 1 as supporting informants. The findings revealed that pre-elderly non-Prolanis diabetes mellitus patients still face obstacles in self-management, such as confusion in dietary regulation, limited access to blood sugar monitoring, barriers to physical exercise, low adherence to medication, and emotional stress. They expressed the need for educational media that is practical, simple, and easy to understand. A booklet was considered suitable because it can be read repeatedly; however, improvements in language, font size, and illustrations are needed to make it more elderly-friendly. In conclusion, booklets are an effective educational medium to enhance understanding and adherence among pre-elderly non-Prolanis patients in managing diabetes mellitus. With adjustments tailored to the characteristics of pre-elderly individuals, booklets have the potential to support independent and sustainable diabetes self-management. Reading list: 32 (2018–2024)Keywords: Self-management, Pre-elderly, Non-Prolanis, Information, Media booklet